Indocyanine-green-embedded PEBBLEs as a contrast agent for photoacoustic imaging - Kim, Gwangseong; Huang, Sheng-Wen; Day, Kathleen C; O'Donnell, Matthew; Agayan, Rodney R; Day, Mark A; Kopelman, Raoul; Ashkenazi, Shai (Journal of biomedical optics, 2007)
Nanoparticles 100 nm in diameter containing indocyanine green (ICG) have been developed as a contrast agent for photoacoustic (PA) imaging based on (photonic explorers for biomedical use by biologically localized embedding PEBBLE) technology using organically modified silicate (ormosil) as a matrix. ICG is an FDA-approved dye with strong optical absorption in the near-infrared (NIR) region, where light can penetrate deepest into biological tissue. A photoacoustic imaging system was used to study image contrast as a function of PEBBLE concentration in phantom objects. ICG-embedded ormosil PEBBLEs showed improved stability in aqueous solution compared with free ICG dye. The particles were conjugated with HER-2 antibody for breast cancer and prostate cancer cell targeting. Initial in vitro characterization shows high contrast and high efficiency for binding to prostate cancer cells. ICG can also be used as a photosensitizer (generating toxic oxygen by illumination) for photodynamic therapy. We have measured the photosensitization capability of ICG-embedded ormosil nanoparticles. This feature can be utilized to combine detection and therapeutic functions in a single agent.